Diffraction by an anisotropic dielectric half-plane a uniform asymptotic PO solution. - Gennarelli, C.
A uniform solution is proposed to, describe the diffraction by a penetrable anisotropic dielectric halfplane illuminated at normal incidence by an electromagnetic plane wave. Resorting to second-order boundary conditions on a sheet simulating a special type of anisotropic dielectric thin layer, a physical optics (PO) approximation for the induced electric and magnetic surface currents is derived. Then, a uniform asymptotic evaluation of the corresponding radiation integral provides the diffracted field in terms of the standard transition function relevant to the uniform theory of diffraction. The effectiveness of the solution is proved by many numerical tests
Keywords: EM wave diffraction; PO approximation; Anisotropic dielectric thin layer; Diffracted field; Electromagnetic plane wave; Induced magnetic surface currents; Normal incidence; Numerical tests; Penetrable anisotropic dielectric half-plane.; Physical optics approximation; Radiation integral; Second-order boundary conditions; Standard transition function; Thin induced surface currents; Uniform asymptotic PO solution; Uniform solution; Uniform theory of diffraction